Public Management in Rural Local Governments: An Assessment of Institutional Differences and Implications. (March 2019) - Helpap, David J.
Rural America often is portrayed in one of two ways. The first recalls quintessential American main streets—safe, friendly, and situated in picturesque landscapes. The second depicts empty storefronts, public health crises, and resentment toward change. Within this complex picture of rural life, however, are municipalities that must be managed. This research examines the use of a professional administrator by rural communities and the degree to which the position is correlated with public expenditures. Results indicate that use of a professional administrator is correlated with population, partisanship, education, and wealth, but its effect on expenditures appears limited.